Contributions to Training in Translation/Localization of Games: A Review of Miguel Ángel Bernal-Merino’s “Translation and Localisation in Video Games: Making Entertainment Software Global” - Morais, Cecília Franco (2020)
In his book “Translation and localisation in video games: making entertainment software global”, Miguel Ángel Bernal-Merino describes and analyses factors which influence the video game localization process, from both the commercial and the translational aspects. The author also traces the historic evolution of the video games localization industry as well as describes the Translation Studies theories and how each one contributes, or could contribute, to studying video game localization. One of the author’s aim is to promote a better collaboration between both sides of the localization process: the industry and the translator. Bernal-Merino’s book contributes to the training of new professional translators or translators who already work on the localization market, since his descriptions and analyses guide and raise the awareness of trainers, scholars and/or professional translators about the problems and challenges to be faced during their work in localization.